2006
DOI: 10.1093/aob/mcl217
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Reductase in Leaves of Cowpea: Cloning of Two cDNAs, Expression and Enzymatic Activity under Progressive Drought Stress, Desiccation and Abscisic Acid Treatment

Abstract: These results demonstrate a noticeable activation in both cultivars of the antioxidant metabolism under a progressive water stress, which involves both GR genes in the case of the susceptible cultivar. Under a fast desiccation, the susceptible cultivar responded later than the resistant one, suggesting a weaker capacity of response versus the resistant one. Exogenous ABA probably acts on GR gene expression via a mediated signal transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 33 publications
1
54
0
2
Order By: Relevance
“…ABA application significantly enhances the expression of GR genes in rice (Kaminaka et al 1998) and cowpea (Contour-Ansel et al 2006). In the present study, exogenous ABA enhanced the expression OsGR2 and OsGR3 in rice roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA application significantly enhances the expression of GR genes in rice (Kaminaka et al 1998) and cowpea (Contour-Ansel et al 2006). In the present study, exogenous ABA enhanced the expression OsGR2 and OsGR3 in rice roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GR is enhanced in plants by drought/desiccation (Contour-Ansel et al 2006;Torres-Franklin et al 2008) and salt (Kaminaka et al 1998). Abscisic acid (ABA) and H 2 O 2 accumulate in plants under salt stress (Moons et al 1995;Montero et al 1997;Tsai et al 2005;Hong et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During abiotic stresses, upon reaction with oxidizing agents, GSH, a tripeptide composed of the amino acids glutamic acid, cystine and glycine (γ-L-Glutamyl-L-cystine glycine), is converted to GSSG [11]. It has been reported that glutathione levels (GSH/GSSG ratio) changes rapidly in response to water deficit, thus helping maintain the redox homeostasis of the cell [12]. In wheat (Triticum sp.)…”
Section: Effects Of 17β-estradiol Application On Stress-related Biochmentioning
confidence: 99%
“…A common consequence of various abiotic stresses, such as drought, salt, heavy metal and other stresses, is the production of reactive oxygen species (ROS) in plant cells and oxidative damage to tissues [10]. Studies have shown a direct correlation between the enhanced antioxidant activities and drought tolerance in various plant species [10] [11] [12]. Treatment of germinating bean (Phaseolus vulgaris) seeds with various concentrations of progesterone, β-estradiol and androsterone resulted in increased activity of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POX) and catalase (CAT) in plants grown under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of water stress reported in the literature on enzyme activities are disputable, depending both on the degree of tolerance of the plant, and on the way of water stress (Contour-Ansel et al 2006). In any case, these systems in overall, help plants growing in adverse environments alleviate the deleterious effect of active oxygen species (AOS) which are produced at increased rates (Jebara et al 2005).…”
mentioning
confidence: 99%